Teaching reading texts on discipline «The profession-oriented foreign language». (Eurasian Journal of Philology Science and Education, 2015)
The article deals with one of the aspects of teaching a foreign language – reading texts on the discipline «Professionally oriented foreign language» on the example of teaching Business English. Reading has always been and will be one of the most essential aspects of language activity, and effective teaching of reading is one of the main objectives of teaching process. The stages of work on the text and their purposes are considered.It is seen that types of exercises depend on the level of students’ language level as well as on the stages. The article also describes the individual work of students with specialty texts which is one of the types of students’ independent work.
Keywords: мature reading; reading with general understanding of the content; linguistic and extralinguistic support; semantic guess; cognitive and receptive stage; creative stage